2020
DOI: 10.1096/fj.201902926r
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulating idiopathic pulmonary fibrosis related alveolar epithelial dysfunction in a human iPSC‐derived air‐liquid interface model

Abstract: Idiopathic pulmonary fibrosis (IPF) is a fatal disease of unknown cause that is characterized by progressive fibrotic lung remodeling. An abnormal emergence of airway epithelial‐like cells within the alveolar compartments of the lung, herein termed bronchiolization, is often observed in IPF. However, the origin of this dysfunctional distal lung epithelium remains unknown due to a lack of suitable human model systems. In this study, we established a human induced pluripotent stem cell (iPSC)‐derived air‐liquid … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 90 publications
(212 reference statements)
0
27
0
Order By: Relevance
“…While multicellular organoids closely capture the minute details of cell-cell and cell-ECM interactions and physiological cellular organization they lack vasculature and air-liquid interface (ALI) [( 206); Figure 2]. Recently, it has been shown that ALI promotes differentiation of human pluripotent stem cell (hPSC)-derived alveolar epithelial progenitor cells into ATII-like cells and reduces their transdifferentiation into ATI cells, which occurs in submerged cultures (207). Stimulation with a pro-fibrotic cocktail results in the loss of SPC + ATII cells paralleled by an increase in MUC5B + goblet-like cells mimicking the bronchialization process occurring in the alveoli of IPF patients (207).…”
Section: In Vivo and In Vitro Models Of Pulmonary Fibrosismentioning
confidence: 99%
See 2 more Smart Citations
“…While multicellular organoids closely capture the minute details of cell-cell and cell-ECM interactions and physiological cellular organization they lack vasculature and air-liquid interface (ALI) [( 206); Figure 2]. Recently, it has been shown that ALI promotes differentiation of human pluripotent stem cell (hPSC)-derived alveolar epithelial progenitor cells into ATII-like cells and reduces their transdifferentiation into ATI cells, which occurs in submerged cultures (207). Stimulation with a pro-fibrotic cocktail results in the loss of SPC + ATII cells paralleled by an increase in MUC5B + goblet-like cells mimicking the bronchialization process occurring in the alveoli of IPF patients (207).…”
Section: In Vivo and In Vitro Models Of Pulmonary Fibrosismentioning
confidence: 99%
“…Recently, it has been shown that ALI promotes differentiation of human pluripotent stem cell (hPSC)-derived alveolar epithelial progenitor cells into ATII-like cells and reduces their transdifferentiation into ATI cells, which occurs in submerged cultures (207). Stimulation with a pro-fibrotic cocktail results in the loss of SPC + ATII cells paralleled by an increase in MUC5B + goblet-like cells mimicking the bronchialization process occurring in the alveoli of IPF patients (207). However, these models still lack biomechanical stimulation (Figure 2).…”
Section: In Vivo and In Vitro Models Of Pulmonary Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, FGF-10 is essential for the survival and proliferation of epithelial stem cell like DASCs (Zuo et al, 2015;Shi et al, 2019), and it can also promote alveologenesis after lung injury (Yuan et al, 2019), while the level of FGF-10 is declined in progressive IPF patients (Chanda et al, 2016). A recent study showed that treatment with IPF-relevant cytokine cocktail (including IL-1β, TGF-β1, TNF-α, IL-8, IL-33, IL-13, IL-4, TSLP, and MCP-1) altered the differentiation direction of alveolar and small airway epithelial stem cells (Schruf et al, 2020). These evidences indicate that the lower engagement of non-AEC2 progenitor/stem cells in alveolar regeneration may also attribute to the unfavorable microenvironment in IPF lungs.…”
Section: Non-aec2 Progenitor/stem Cells May Not Adapt the Abnormal MImentioning
confidence: 99%
“…When suspended in Matrigel, these cells generated structures similar to purified human AT2 cells under organotypic culture (Barkauskas et al, 2013;Zacharias et al, 2018). This morphologic property has allowed for modeling of numerous alveolar pathologies (Hiemstra et al, 2018;Heo et al, 2019;Shafa et al, 2018;Korogi et al, 2019;Leibel et al, 2019;Porotto et al, 2019;Schruf et al, 2020). However, the time and experience required to differentiate iPSCs properly towards a distal lung lineage are not trivial.…”
Section: Introductionmentioning
confidence: 99%